Synovium as a widespread pathway to the adjacent joint in undifferentiated high-grade pleomorphic sarcoma of the tibia: A case report. Issue 8 (February 2018) - Li, Xiaona; Zhang, Zekun; Latif, Mahrukh; Chen, Wei; Cui, Jianling; Peng, Zhigang
Abstract: Rationale: Undifferentiated high-grade pleomorphic sarcoma (UPS), originated from bone, is a rare tumor, accounting for 2% to 5% of all primary maligment bone neoplasms. Skip lesion can be found in undifferentiated high-grade pleomorphic sarcoma of bone (UPS-B). However, the direct invasion across the articular synovium to bone has not been reported previously. Patient concerns: We report an unusual case of a 65-year-old man complained of a year history of pain, swelling, and limitation of activity in the left knee joint. At the proximal tibia, there was extensive invasion of articular synovium, which provides a direct anatomic pathway for the tumor invasion to the adjacent bone, including patella and femoral condyle. Diagnoses: Magnetic resonance imaging was important in defining the marrow involvement and joint invasion, including the thickening articular synovium. Subsequent pathological examination confirmed the diagnosis of UPS. Interventions: The patient underwent an extensive resection of the knee joint, except for the patellar. Outcomes: After operation, routine chemotherapy was performed. Unfortunately, half a year later, soft tissue swelling of whole thigh was found. Then this patient came our hospital again. Positron emission tomography imaging showed there was recurrence of UPS with lung metastasis. A week later, this patient died. Lessons: In contrast to frequent infiltration pathway, the articular synovium as a media for this tumor spread is rare. This study adds a better understanding of this direct invasion way to the medical literature.